Stylized facts of Euroland's business cycle - Jörg Döpke (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
The paper presents some stylized facts of Euroland's business cycle using aggregated data. The main results are: The determination of turning points in Euroland's business cycle is not very sensitive to the detrending method used, although the level of the recent output gap depends on it. Investment, net exports and stock building explain the largest share of the swings in real GDP. The types of expenditures - except for net exports - are pro-cyclical with almost no lag or lead. The results for monetary variables are unclear, most of them show no clear-cut cyclical behavior. Prices are counter-cyclical, whereas labor productivity and real wages are pro-cyclical. The cyclical component of industrial production in all member countries shows a positive and over time increasing correlation coefficient with the one in the rest of Euroland.
Keywords: E32; 330; Business Cycles; Stylized Facts; European Monetary Union; Konjunktur; Zeitreihenanalyse; Konjunkturprognose; Prognoseverfahren; Schätzung; Europäische Wirtschafts- und Währungsunion; EU-Staaten